TaPR1 Interacts With TaTLP1 via the αIV Helix to Be Involved in Wheat Defense to Puccinia triticina Through the CAPE1 Motif - Wang, Fei; Shen, Songsong; Zhao, Cunpeng; Cui, Zhongchi; Meng, Linshuo; Wu, Wenyue; Liu, Daqun; Wang, Haiyan (Frontiers in Plant Science, 2022)
Pathogenesis related (PR) proteins perform important roles in plant defense response and systemic acquired resistance (SAR). PR1 has antifungal activity against many plant pathogens. In our previous study, RNA sequencing (RNA-seq) was conducted on resistant wheat line TcLr19 and sensitive wheat cultivar Chinese Spring inoculated with Puccinia triticina (Pt) race PHNT. In this study, seven salicylic acid (SA)-induced TaPR1 genes involved in plant disease resistance were found in the RNA-seq library. Quantitative PCR (qPCR) results showed that TaPR1-4 was most induced by Pt among these seven TaPR1 genes in the incompatible interaction. Yeast two-hybrid (Y2H) results showed that TaPR1-4 interacted with TaTLP1 via the αIV helix. Protein-mediated phenotyping assays in vivo and antifungal activity in vitro demonstrated that wheat leaves infiltrated with pure TaPR1-4 protein developed significantly less disease compared to control leaves. This effect was correlated with a strong increase in defense gene expression, and resistance activity was dependent on the CAPE1 motif located in the C-terminal region of TaPR1-4. These findings increase current knowledge regarding the interaction of TaPR1 and TaTLP1, and provide new insights on the role of TaPR1 protein in the resistance of wheat to Pt.